Methodology of project management at implementation of projects of high-rise construction - Papelniuk Oksana (E3S Web of Conferences, 2018)
High-rise construction is the perspective direction in urban development. An opportunity to arrange on rather small land plot a huge number of the living and commercial space makes high-rise construction very attractive for developers. However investment projects of high-rise buildings’ construction are very expensive and complex that sets a task of effective management of such projects for the company builder. The best tool in this area today is the methodology of project management, which becomes a key factor of efficiency.